Did Turkey Experience Reductions in Air Pollution During The Covid-19 Lockdown and Partial Lockdown? - İsmet Yener; Kazım Onur Demirarslan (Doğal Afetler ve Çevre Dergisi, 2024)
Air pollution, one of humanity's essential environmental problems due to the increasing population and urbanization, negatively affects the ecosystem and public health. During reduced human activity, such as martial law, war, and pandemics like COVID-19, improvements in air quality may be observed due to diminished anthropogenic impact. The novel coronavirus, COVID-19, has caused widespread illness and fatalities. The World Health Organization (WHO) declared a state of emergency at the end of December 2019 following the first recognition of the virus in Wuhan. The Turkish government declared this state on March 11, 2020, and implemented some measures, including a lockdown (LD) and a partial lockdown (PLD), to protect public and human health. The present study aims to determine the impact of LD and PLD on the air quality of fourteen selected cities in Turkey that participated in all LDs during the state of emergency on weekends and national and religious holidays. The hourly air quality data used in the study were collected from 105 air monitoring stations in fourteen cities. The non-parametric Kruskal Wallis test, followed by the Dunn's Bonferroni test for pairwise comparison, was employed to determine the differences in air quality between years. The findings indicated significant reductions in air pollution during LD and PLD: 21.1-40.3% and 8.9-29.8% in PM10, respectively, and 30.2-50.8% and 2.6-22.4% in NOx, respectively. SO2 and CO also varied significantly. While the changes in SO2 during LD and PLD went from 0.0% to 5.7% and -2.4% to 1.2%, respectively, those in CO ranged from -6.6% to 29.6% and 1.3% to 33.2%, respectively.